2022
DOI: 10.1126/sciadv.abl9754
|View full text |Cite
|
Sign up to set email alerts
|

Sequential consumer choice as multi-cued retrieval

Abstract: Whether adding songs to a playlist or groceries during an online shop, how do we decide what to choose next? We develop a model that predicts such open-ended, sequential choices using a process of cued retrieval from long-term memory. Using the past choice to cue subsequent retrievals, this model predicts the sequential purchases and response times of nearly 5 million grocery purchases made by more than 100,000 online shoppers. Products can be associated in different ways, such as by their episodic association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Our work contributes to the emerging body of research that offers researchers a naturalistic search domain to study active learning (Bramley et al, 2018; Hornsby & Love, 2022; Liefgreen et al, 2020; Z. H. Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our work contributes to the emerging body of research that offers researchers a naturalistic search domain to study active learning (Bramley et al, 2018; Hornsby & Love, 2022; Liefgreen et al, 2020; Z. H. Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent "big data" analysis of over 135,000 sequential grocery purchase decisions, Hornsby and Love (2022) showed that the decision to select an item for purchase from an online store is cued by recently selected items. In their model, the similarity between potential choices and previously selected items is based on a comparison across different representations.…”
Section: What Are the Implications For Real-world Categorization?mentioning
confidence: 99%